2019
DOI: 10.1101/520247
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measuring vision using innate behaviours in mice with intact and impaired retina function

Abstract: Measuring vision in rodents is a critical step for understanding vision, improving models of human disease, and developing therapies. Established behavioural tests for perceptual vision, such as the visual water task, rely on learning. The learning process, while effective for sighted animals, can be laborious and stressful in animals with impaired vision, requiring long periods of training. Current tests that that do not require training are based on sub-conscious, reflex responses (e.g. optokinetic nystagmus… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 55 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…While we did not detect changes in ERGwave amplitudes in rd1 TN-XL mice treated at such late stages of degeneration, a modest improvement of ERG recordings was detected in rd10 mice following the treatment. Notably, despite ERG amplitudes remaining lower than in wild-type mice, the significant improvement in visually-driven behavior suggests that the potential benefits for the daily tasks of RP patients may be achievable even at the late stages of the disease [51]. It is very challenging to assess the effectiveness of vision therapy, even in patients.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not detect changes in ERGwave amplitudes in rd1 TN-XL mice treated at such late stages of degeneration, a modest improvement of ERG recordings was detected in rd10 mice following the treatment. Notably, despite ERG amplitudes remaining lower than in wild-type mice, the significant improvement in visually-driven behavior suggests that the potential benefits for the daily tasks of RP patients may be achievable even at the late stages of the disease [51]. It is very challenging to assess the effectiveness of vision therapy, even in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among visual stimuli we selected a bright flash and a looming object. We have previously shown that these two stimuli evoke distinct and opposite behavioural responses, with the former inducing an increase in locomotor activity while the latter abolishes locomotion by inducing freezing behaviour [7].…”
Section: Measuring Multiple Motor Actions Provides a Higher Dimensionmentioning
confidence: 99%
“…This increase in specificity was particularly remarkable when comparing behavioural responses to a loud sound and a visual looming. It has been previously shown that both stimuli induce escape to a shelter or freeze when the shelter is not present [7,36]. As a result the responses to these stimuli have been considered equivalent and no attempts have been made to differentiate them.…”
Section: The Mapping Between Stimulus and Response Is Not Uniquely Dementioning
confidence: 99%
See 2 more Smart Citations